Gotong Royong in Strengthening the Roles of Government, Non-Governmental Organizations, and the Private Sector in Facilitating the Family Planning Program (KB) - Pambajeng Luluh Dyah Pangestu; Nadya Chalista Primadan; Ruben Pratama; Rosadi; Delon Septo Aditya; Noval Agustin Saputra; Juspriadi; Suriano; Ardianson; Ahmad Sopian; Ariatul (PT Polstac Repositori Riset, 2026)
Background: Habaring Hurung Urban Village is located near Katingan Regency, which presents specific geographical and demographic challenges. Male participation in family planning programs remains low, while there is also a need to improve the quality of life of families with toddlers, adolescents, and the elderly. Contribution: Socialization of the Kampung KB concept was conducted to increase community awareness and understanding of the family planning program. This was followed by the establishment of agreements with community leaders to ensure local support and commitment to the initiative. Finally, a Family Planning Management Team at the urban village level was formally established through a decree issued by the Head of the Urban Village. Method: The program applied a gotong royong approach through regular community clean-up activities to improve environmental cleanliness and strengthen social solidarity in Habaring Hurung Urban Village. Results: Based on the activities that have been carried out, it can be concluded that the spirit of gotong royong in Habaring Hurung Urban Village remains very strong and effective in helping to alleviate the community’s burdens. Conclusion: To enhance the effectiveness of gotong royong activities, it is recommended that the dissemination of information regarding schedules and types of activities be conducted more intensively so that community participation can be further increased.